NAME CHANGE PROCEDURE IN THE MAJALENGKA DISTRICT COURT SYSTEM CLASS II B: A REVIEW OF CIVIL PROCEDURE LAW - Priatna, Muh. Rizki; Praja, Angga Nugraha; Alfarizi, Abram Nabil; Priyohastomo, Hadi Maulana; Putra Kusmana, Daffa Adiesta; Amelia, Khodijah Sefty; Taufik F, Dadan (Hukum Responsif, 2025)
Background. Name change is one of the civil rights guaranteed by Indonesian law, the implementation of which is regulated through a court determination mechanism. In practice, every citizen who wants to change their name is required to apply to the District Court according to their domicile. Aims. This study aims to analyze the name change procedure in the judicial system in the Majalengka District Court Class II B. The formulation of the research problem is focused on the name change procedure. Methods. The research method employed is empirical juridical, combining the study of laws and regulations as secondary data with the results of interviews and observations in court as primary data. Result. The results of the study showed that the name change procedure was carried out through the submission of an application, examination of supporting documents, trial, and appointment of judges. Conclusion. The process is primarily based on positive legal provisions; however, obstacles include a lack of public understanding of the requirements and procedures that must be met, as well as the lengthy processing time resulting from incomplete documents that are not fulfilled from the outset. Implementation. This research is expected to contribute to improving judicial services and become a reference for people who want to apply for a name change according to legal procedures